2003
DOI: 10.1099/mic.0.26303-0
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a soil-derived bacterial consortium degrading 4-chloroaniline

Abstract: A bacterial consortium comprising four different species was isolated from an Indonesian agricultural soil using a mixture of aniline and 4-chloroaniline (4CA) as principal carbon sources. The four species were identified as Chryseobacterium indologenes SB1, Comamonas testosteroni SB2, Pseudomonas corrugata SB4 and Stenotrophomonas maltophilia SB5. Growth studies on aniline and 4CA as single and mixed substrates demonstrated that the bacteria preferred to grow on and utilize aniline rather than 4CA, although b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 56 publications
2
40
0
2
Order By: Relevance
“…The pattern generated with API 20NE test was a good match with Xanthomonas maltophilia. Similar results were obtained by Radianingtyas and co-workers (22). These authors identified the particular microorganisms of consortium degrading 4-chloroaniline.…”
Section: Isolation and Identification Of Strain Degrading Aromatic Cosupporting
confidence: 86%
“…The pattern generated with API 20NE test was a good match with Xanthomonas maltophilia. Similar results were obtained by Radianingtyas and co-workers (22). These authors identified the particular microorganisms of consortium degrading 4-chloroaniline.…”
Section: Isolation and Identification Of Strain Degrading Aromatic Cosupporting
confidence: 86%
“…have not yet proved able to hydrolyze chloropropham, although they are known for their chloroaniline-degrading capacities (10,26,36). Enrichment of the sludge and soil inocula in the presence of a solid matrix led to microbial communities with a higher species richness and evenness.…”
Section: Vol 77 2011 Planktonic Versus Biofilm Catabolic Communitiementioning
confidence: 99%
“…Therefore, many efforts have been undertaken to isolate bacteria capable of biodegradation of chloroanilines (Surovtseva et al, 1985;Loidl et al, 1990). Although some microorganisms have been reported to have biodegradability towards chloroanilines, their limitation is that they are unable to grow on chloroanilines as sole sources of carbon and nitrogen Reber et al, 1979;You and Bartha, 1982;Radianingtyas et al, 2003). Only recently, 3-chloroaniline-degrading Comamonas testosteroni strain I2gfp capable of utilizing 3-chloroaniline as a sole source of carbon and nitrogen was isolated (Boon et al, 2000).…”
Section: Troductionmentioning
confidence: 99%
“…Nonetheless, under certain growth conditions, a few microorganisms have been reported to be able to grow on 4-chloroaniline as a sole carbon and nitrogen source. For instance, previous studies stated that the bacterial isolations were successful only after they were cocul-tivated or induced in the presence of aniline or another cosubstrate, for example, glucose, for some periods of time (Zeyer and Kearney, 1982;Radianingtyas et al, 2003;Travkin et al, 2003). In the current study, we used a defined bacterial consortium, reconstructed from strains isolated from a putatively herbicide-contaminated site, to investigate 4-chloroaniline (4CA) metabolism in the presence of aniline.…”
Section: Troductionmentioning
confidence: 99%